First Report of Cladosporium colocasiae Causing Leaf Spot on Taro (Colocasia esculenta) in Mexico - Vásquez-López, A.; Palacios Torres, Rogelio Enrique; Montiel-Frausto, L. B.; Medero Vega, V. R.; Lima, N. B.; Camacho-Tapia, M.; Tovar-Pedraza, Juan Manuel (The American Phytopathological Society, 2018)
In September 2017, symptoms of leaf spot were observed on approximately 80% of taro (Colocasia esculenta var. antiquorum) plants at a commercial field located in San Juan Bautista Tuxtepec, Oaxaca, Mexico. Lesions on diseased leaves were dark brown and oval to irregular, sometimes coalescing to cover large areas of the leaf surface. To isolate the fungus, small fragments from adjacent tissue to lesions of symptomatic leaves were excised and surface disinfested by immersion in 1% NaOCl for 2 min, rinsed three times in sterile distilled water, dried in blotter paper, and placed in Petri plates containing potato dextrose agar (PDA) amended with ampicillin (20 mg/liter) and rifampicin (20 mg/liter). The plates were incubated at 25°C under constant white light for 8 days, and then mycelial plugs were aseptically transferred to fresh PDA medium.